Could Digital Means Replace Real-Life Property Viewings? A Comparative Analysis of Virtual and Augmented Reality in Real Estate Marketing - Christina A. CHRISTOPOULOU; Katarzyna KOPECKA-PIECH (Communications of International Proceedings, 2021)
Viewings of real estate properties can be time-consuming and require multiple visits by interested buyers. There are two models of buying or trying to find property: 1) physical/material, and 2) virtual/digital searching. Immersive technology aids the development of different ways of viewing a property. The main focus of this research is to explore whether the material/physical activity could be replaced in real estate marketing by virtual/digital viewing, specifically when using Virtual Reality (VR) or Augmented Reality (AR) mobile apps, and/or to what extent. Mixed qualitative methodology was applied in the study: pre-questionnaire, experimental use of selected mobile apps and post-interviews including application of mobile app rating scales. The VR app ratings were better across all evaluation categories. The results indicate that the AR app was better to use when looking for properties to rent, whereas the VR when buying. The VR app was more engaging, coinciding with the average satisfaction ratings. The AR app was simpler and unambiguous. 14 out of 15 informants would not buy a property just by using any of the apps. However, almost half of the informants mentioned that using these apps is better than seeing photos of the properties.
Keywords: Virtual Reality; Augmented Reality; Mobile Apps; Real Estate